Pengaruh Asal Sekolah dan Jurusan Terhadap Hasil Belajar Pengantar Dasar Matematika Mahasiswa Fakultas Tarbiyah UIN Mataram - Parhaini Parhaini (Hikmah: Journal of Islamic Studies, 2017)
One of the courses at the faculty of Tarbiyah of the UIN Mataram that requires analytical skills of critical and creative is the Introduction to Basic Mathematics (PDM). This is because this course is the basic subject that requires prior knowledge that is qualified. Therefore, it needs to be studied on how the influences of the high school backgrounds and the majors of the study in the university on the learning outcomes of the PDM. The data of the research are 80 students majoring in Education of Mathematics and Education of Science who are from Islamic high school (MA) andhighschool(SMA). Thedataareobtainedbytheclusterrandom sampling technique and analyzed with a 2x2 factorial design. The ANAVA test results show that the high school backgrounds have real impact on learning outcomes of the PDM, while the majors have no significant effect on the learning outcomes of the PDM. What is more, the research also shows that the learning outcomes of the PDM of the students from the SMA are better than those of the students from theMA. Keywords: learning outcomes, attitude, and competence. One of the courses at the faculty of Tarbiyah of the UIN Mataram that requires analytical skills of critical and creative is the Introduction to Basic Mathematics (PDM). This is because this course is the basic subject that requires prior knowledge that is qualified. Therefore, it needs to be studied on how the influences of the high school backgrounds and the majors of the study in the university on the learning outcomes of the PDM. The data of the research are 80 students majoring in Education of Mathematics and Education of Science who are from Islamic high school (MA) andhighschool(SMA). Thedataareobtainedbytheclusterrandom sampling technique and analyzed with a 2x2 factorial design. The ANAVA test results show that the high school backgrounds have real impact on learning outcomes of the PDM, while the majors have no significant effect on the learning outcomes of the PDM. What is more, the research also shows that the learning outcomes of the PDM of the students from the SMA are better than those of the students from theMA. Keywords: learning outcomes, attitude, and competence.